2012
DOI: 10.7475/kjan.2012.24.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Level of Knowledge on Evidence-based Infection Control and Influencing Factors on Performance among Nurses in Intensive Care Unit

Abstract: Purpose: This study was to identify the level of knowledge and performances on evidence-based infection control and influencing factors on performance among nurses in intensive care unit. Methods: A descriptive crosssectional survey design was used. Two hundred thirty-nine nurses at intensive care units were conveniently recruited from seven hospitals located in Seoul and Kyounggi province. Data were collected with a questionnaire survey about evidence-based infection control. Data were analyzed using SPSS/WIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
2
6
0
3
Order By: Relevance
“…This study was conducted in 14 intensive care units of health and education centers at Guilan hospitals. The mean score of nurses’ knowledge was 4.63 ± 1.708 (51.4% mean correct answers); however, various studies have reported the mean scores to be 41.2% (Blot et al) , 45.1% (Labeau et al) , 59.9% (Jansson et al) , 65.6% (Lin et al) , 78.1% (El‐Khatib et al) , 53.1% (Yoo et al) , and 51.9% (Bagheri‐Nesami et al) . Variation in the scores may be due to the differences between models of health care , the routine tasks of intensive care nurses, lack of national and international guidelines, and lack of consistent policy .…”
Section: Discussionmentioning
confidence: 98%
“…This study was conducted in 14 intensive care units of health and education centers at Guilan hospitals. The mean score of nurses’ knowledge was 4.63 ± 1.708 (51.4% mean correct answers); however, various studies have reported the mean scores to be 41.2% (Blot et al) , 45.1% (Labeau et al) , 59.9% (Jansson et al) , 65.6% (Lin et al) , 78.1% (El‐Khatib et al) , 53.1% (Yoo et al) , and 51.9% (Bagheri‐Nesami et al) . Variation in the scores may be due to the differences between models of health care , the routine tasks of intensive care nurses, lack of national and international guidelines, and lack of consistent policy .…”
Section: Discussionmentioning
confidence: 98%
“…The low knowledge scores reflect the fact that nurses need special training and qualification in ICU. The acquisition of a specialized ICU qualification was associated with a significantly better knowledge score on VAP (Yoo, et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, only 26% of nurses who participated in the study provided the correct answer related to the use of closed versus open suctioning pre‐intervention. Many studies revealed the low percentage of nurses who knew the recommended route for tracheal intubation, frequency of ventilator circuit changes, type of suction systems, frequency of suction system changes, type of humidification system and frequency of humidifier changes (Blot et al , ; Llauradó et al , ; Yoo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…관계가 있었고 [14] [15], 감염관리에 대한 인지도에 비해 수행도가 낮은 수준으로 보고되었으며, 수 행도가 낮은 원인으로 간호사의 업무과다로 인한 시간부족과 설비 및 물품부족을 들었다 [16] [17].…”
Section: 선행연구에 의하면 감염관리에 대한 지식수준과 인지도 및 간호실무 간에는 유의한 양의 상관unclassified